The exotic μ~ —» e~ conversion in Nuclei: An Interplay of Atomic, Nuclear and Particle Physics. - Kosmas, T. S. (HNPS Advances in Nuclear Physics, 2019)
The partial rates of all kinematically accessible channels (for coherent and incoherent processes) of the exotic μ~ —» e~ conversion in the currently interesting nuclei 27Al, 4 8Ti, and 2 0 8Pb are investigated. The assumed muon-number violation involves exchange of various particles in conventional extentions of the standard model and in minimal supersymmetric models with R-parity conserving and R-parity violating interactions. The transition matrix elements obtained are used to extract very severe constraints for the flavor violation parameters entering the effective Lagrangians resulting in the framework of specific particle models.